2009
DOI: 10.1007/s10553-010-0166-y
|View full text |Cite
|
Sign up to set email alerts
|

Solid-acid alkylation catalysts based on modified type Y zeolites in polycation-decationized forms

Abstract: Industrial procedures for the production of alkylate are associated with use of dangerous and toxic liquid catalysts. Developments are being made worldwide to convert the alkylation process to solid-acid catalysts. These catalysts are characterized, however, by a short service life. The potential for improvement in the operational properties of solid-acid catalysts by the introduction of small amounts of promoters to the reaction is examined.Throughout the world, the portion of alkylate in the overall consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…www.prkm.co.uk Solid acids, and particularly solid superacids, can be used instead of conventional catalysts in organic transformations [2]. It has been observed that the solid superacids are useful catalysts for the isomerisation [3,4], alkylation [5][6][7], amidation [8], oligomerisation [9], esterification [10][11][12][13][14][15] and the hydrolysis of cellulose [16,17]. Different kinds of solid superacid have been developed: (i) mounted acids which were obtained by fixation of a liquid acid such as SbF 5 on supports with high surface area; (ii) combined acids which were obtained by the combination of aluminum halides with metal salts such as CuCl 2 or CuSO 4 ; (iii) sulfate-promoted metal oxides such as SO 4…”
Section: Introductionmentioning
confidence: 99%
“…www.prkm.co.uk Solid acids, and particularly solid superacids, can be used instead of conventional catalysts in organic transformations [2]. It has been observed that the solid superacids are useful catalysts for the isomerisation [3,4], alkylation [5][6][7], amidation [8], oligomerisation [9], esterification [10][11][12][13][14][15] and the hydrolysis of cellulose [16,17]. Different kinds of solid superacid have been developed: (i) mounted acids which were obtained by fixation of a liquid acid such as SbF 5 on supports with high surface area; (ii) combined acids which were obtained by the combination of aluminum halides with metal salts such as CuCl 2 or CuSO 4 ; (iii) sulfate-promoted metal oxides such as SO 4…”
Section: Introductionmentioning
confidence: 99%